JPATS 2021
DOI: 10.25259/jpats_11_2021
|View full text |Cite
|
Sign up to set email alerts
|

Management of lung cancer in Africa: Underdiagnosis and poor access to treatment – A close look at Nigeria and West African Sub-region

Abstract: Lung cancer is of public health importance and imposes a great deal of socioeconomic and disease burden on the West African subregion and Nigeria in particular. It is one of the most common cancers worldwide and accounts for 11.4% of all new cancers. In this review, we did not find any well-coordinated lung cancer registry in either Nigeria or any other West African country. For us to attain any meaningful level of the interventional plan to address any identifiable deficiencies in the treatment of lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
(81 reference statements)
0
17
0
Order By: Relevance
“…Okonta et al [ 47 ] reviewed the available Nigerian and west African sub-region data, and linked the LC situation and poorer prognosis in each country with environmental, genetic and toxic aspects, finding differences between published studies. While Soussi et al [ 48 ] found based on a Tunisian cohort that age at diagnosis, PS, histological type, TNM stage, with haemoglobin level, leucocyte count, calcium, lactate dehydrogenase and levels of alkaline phosphatase are the independent prognostic factors related to survival.…”
Section: Discussionmentioning
confidence: 99%
“…Okonta et al [ 47 ] reviewed the available Nigerian and west African sub-region data, and linked the LC situation and poorer prognosis in each country with environmental, genetic and toxic aspects, finding differences between published studies. While Soussi et al [ 48 ] found based on a Tunisian cohort that age at diagnosis, PS, histological type, TNM stage, with haemoglobin level, leucocyte count, calcium, lactate dehydrogenase and levels of alkaline phosphatase are the independent prognostic factors related to survival.…”
Section: Discussionmentioning
confidence: 99%
“…There is, therefore, a need to investigate probable environmental, cultural or genetic factors driving these tumours in our locality. Also, the absence of lung cancer in the top five seen in Africa and Nigeria may indicate its lower prevalence in the African population or underdiagnosis of these cases [6,7,16]. The role of unsafe sexual practices on the high proportion of cervical cancer seen may need validation [3].…”
Section: Discussionmentioning
confidence: 99%
“… 1 South and North African countries have a greater prevalence of lung cancer than East and West Africa. 4 This malignancy is known to have a poor survival rate, but an improvement in the overall survival rates can be attributed to personalized treatment and the introduction of targeted therapy. 5 In a Scandinavian study, an improvement in 1‐year survival was observed in nonsquamous cell carcinoma regardless of the stage of the malignancy at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 Inadequate management and underdiagnosis of lung cancer are alarming issues in the health care of African settings. 4 , 10 Access to cancer screening and treatment is one of the major challenges in Kenya. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation